Effects of perioperative steroid use on surgical stress and prognosis in patients undergoing hepatectomy: a systematic review and meta-analysis of randomized controlled trials - Zhong, Furui; Yang, Hua; Peng, Xuefeng; Zeng, Kerui (Frontiers in Pharmacology, 2024)
The objective of this study was to evaluate the clinical effects of perioperative steroid hormone usage in hepatectomy patients through a comprehensive systematic review and meta-analysis. Prospective randomized controlled trials (RCTs) investigating the perioperative use of steroid hormones in hepatectomy were systematically searched using various databases including PubMed, Medline, Embase, Cochrane library, Chinese Biomedical Literature Database, Wanfang Database, and CNKI database. Two researchers independently screened and extracted data from selected studies. Data analysis was performed using RevMan 5.3 software. The results revealed significantly lower levels of total bilirubin (SMD=-0.7; 95%